Repurposing Combination Therapy of Voacamine With Vincristine for Downregulation of Hypoxia-Inducible Factor-1α/Fatty Acid Synthase Co-axis and Prolyl Hydroxylase-2 Activation in ER+ Mammary Neoplasia - Singh, Lakhveer; Roy, Subhadeep; Kumar, Anurag; Rastogi, Shubham; Kumar, Dinesh; Ansari, Mohd. Nazam; Saeedan, Abdulaziz S.; Singh, Manjari; Kaithwas, Gaurav (Frontiers in Cell and Developmental Biology, 2021)
The current study investigated the role of combination therapy with voacamine and vincristine in preventing mammary gland carcinoma through prolyl hydroxylase-2 activation. Prolyl hydroxylase-2 activation leads to the downregulation of hypoxia-inducible factor-1α and fatty acid synthase. Overexpression of hypoxia-inducible factor-1α and fatty acid synthase has been previously reported in solid tumors of the mammary gland. After screening a battery of natural compounds similar to vincristine, voacamine was selected as a possible prolyl hydroxylase-2 activator, and its activity was evaluated using a 7,12-dimethylbenz[a]anthracene-induced rat model. The combination therapy was evaluated for cardiac toxicity using a hemodynamic profile. Angiogenic markers were evaluated by carmine staining. Monotherapy and combination therapy were also evaluated for liver and kidney toxicity using hematoxylin and eosin staining. The antioxidant potential was delineated using oxidative stress markers. The serum metabolomic profile was studied using NMR spectroscopy, and the disruption of fatty acids was evaluated using gas chromatography. Western blotting of proteins involved in hypoxic pathways was performed to decipher the action of therapy at the molecular level. Immunoblotting analysis validated that combination therapy has potential toss with prolyl hydroxylase-2 activity and thus initiates proteolytic degradation of hypoxia-inducible factor-1α and its consequent effects. Combination therapy also stimulated programmed cell death (apoptosis) in rapidly dividing cancer cells. The present study explored the role of voacamine inactivation of prolyl hydroxylase-2, which can decrease the overexpression of hypoxia-inducible factor-1α and fatty acid synthase in mammary gland carcinoma cells.